Acute Recurrent and Chronic Pancreatitis as Initial Manifestations of Cystic Fibrosis and Cystic Fibrosis Transmembrane Conductance Regulator–Related Disorders. Issue 7 (August 2019) - Baldwin, Christina; Zerofsky, Melissa; Sathe, Meghana; Troendle, David M.; Perito, Emily R.
Abstract : Objectives: Recurrent pancreatitis is considered a rare manifestation of cystic fibrosis transmembrane conductance regulator (CFTR) dysfunction; this case series highlights that pancreatitis can be a presenting symptoms of cystic fibrosis (CF) or a CFTR-related disorder (CFTR-RD). Methods: Retrospective review of patients younger than 30 years diagnosed as having acute recurrent pancreatitis (ARP) or chronic pancreatitis (CP) and subsequently diagnosed as having CF or CFTR-RD. Results: Among 18 patients, median time from diagnosis of ARP/CP to diagnosis of CF was 0.4 years (range, 0–33 years). Eight were classified as having CF by elevated sweat chloride testing (SCT). Five had intermediate SCT (30–59 mmol/L) with 2 pathogenic mutations. Five had CFTR-RD with intermediate SCT and 0 to 1 pathogenic mutations. Eight patients (44%) had exocrine pancreatic insufficiency, and pancreatic fluid collections were more common in this group. Based on the CFTR mutation, 6 patients were eligible for CFTR potentiator therapy, although none received it during the study period. Nine of the 18 had ≥1 other likely CF manifestations, including sinusitis (33%), nasal polyps (11%), pneumonia (22%), and gallbladder disease (22%). Conclusions: Cystic fibrosis or CFTR-RD can present as ARP/CP. Complete diagnostic testing for CFTR-RD in patients with ARP/CP will broaden treatment options and help to identify comorbid illness.